Kellogg on integrated marketing - Iacobucci, Dawn; Calder, Bobby (s/c: s/e)
Sus temas principales son: Overview of kellogg on integrated marketing,What is integrated marketing?, the tao of costumer loyalty: Getting to my Brand, my Way, Using interaction maps to create brand experiences and relationsships, strategies for viral marketing, acquiring the right customers , database sub-segmentation, customer profitability and diagnosing a customer portafolio
Incluye bibliografía
Keywords: Marketing; Mercadeo